Identification of early-onset photoreceptor degeneration in transgenic mouse models of Alzheimer's disease - Jie Zhang (Elsevier, 2021)
Summary: Light sensitivity of the vertebrate retina relies on the integrity of photoreceptors, including rods and cones. Research in patients with Alzheimer's disease (AD) and in AD transgenic mice reports that accumulated amyloid-β (Aβ) plaques in the retina are toxic to retinal neurons. Moreover, Aβ plaques are deposited around the rods and cones, yet photoreceptor anomalies remain unclear in AD. Here, we identify the progressive degeneration of rods and cones characterized by impaired expression of phototransduction proteins, morphological alterations, functional deficits, and even cell loss. Furthermore, we demonstrate that cell senescence and necroptosis were involved in rod degeneration. Importantly, using in vivo scotopic electroretinogram, we detected rod degeneration in early-stage AD transgenic mice before Aβ plaques were observed in the brain. Moreover, we demonstrate that rod degeneration was among the earliest AD retinal manifestations compared with other types of retinal neurons. Overall, our study is the first to identify and detect in vivo, early-onset photoreceptor degeneration in AD.